Store‐operated calcium entry controls innate and adaptive immune cell function in inflammatory bowel disease - Letizia, Marilena; Wang, Yin‐Hu; Kaufmann, Ulrike; Gerbeth, Lorenz; Sand, Annegret; Brunkhorst, Max; Weidner, Patrick; Ziegler, Jörn Felix; Böttcher, Chotima; Schlickeiser, Stephan; Fernández, Camila; Yamashita, Megumi; et al. (EMBO molecular medicine, 2022)
Inflammatory bowel disease (IBD) is characterized by dysregulated intestinal immune responses. Using mass cytometry (CyTOF) to analyze the immune cell composition in the lamina propria (LP) of patients with ulcerative colitis (UC) and Crohn's disease (CD), we observed an enrichment of CD4 + effector T cells producing IL‐17A and TNF, CD8 + T cells producing IFNγ, T regulatory (Treg) cells, and innate lymphoid cells (ILC). The function of these immune cells is regulated by store‐operated Ca 2+ entry (SOCE), which results from the opening of Ca 2+ release‐activated Ca 2+ (CRAC) channels formed by ORAI and STIM proteins. We observed that the pharmacologic inhibition of SOCE attenuated the production of proinflammatory cytokines including IL‐2, IL‐4, IL‐6, IL‐17A, TNF, and IFNγ by human colonic T cells and ILCs, reduced the production of IL‐6 by B cells and the production of IFNγ by myeloid cells, but had no effect on the viability, differentiation, and function of intestinal epithelial cells. T cell‐specific deletion of CRAC channel genes in mice showed that Orai1 , Stim1 , and Stim2 ‐deficient T cells have quantitatively distinct defects in SOCE, which correlate with gradually more pronounced impairment of cytokine production by Th1 and Th17 cells and the severity of IBD. Moreover, the pharmacologic inhibition of SOCE with a selective CRAC channel inhibitor attenuated IBD severity and colitogenic T cell function in mice. Our data indicate that SOCE inhibition may be a suitable new approach for the treatment of IBD. Synopsis The immune cell composition, signaling cascades, and cytokine networks controlling inflammation in therapy‐refractory inflammatory bowel diseases (IBD) remain incompletely understood. The colon lamina propria (LP) of ulcerative colitis (UC) and Crohn's disease (CD) patients is enriched with CD4 + and CD8 + T cells, IL‐17‐producing innate immune cells (ILC) and Treg cells. Pharmacological inhibition of store‐operated Ca 2+ Entry (SOCE) inhibits the production of proinflammatory cytokines and certain activation markers by human LP T cells, B cells, ILCs and myeloid cells. Inhibition of SOCE does not impair the differentiation and function of human or mouse intestinal epithelial cells in colonic organoid cultures. Pharmacologic inhibition of SOCE or T cell‐specific deletion of the SOCE genes Orai1 and Stim1 in T cells ameliorates intestinal inflammation in mouse models of colitis. SOCE is an important regulator of intestinal immune cell function and a potential drug target for the treatment of IBD. Graphical Abstract The immune cell composition, signaling cascades, and cytokine networks controlling inflammation in therapy‐refractory inflammatory bowel diseases (IBD) remain incompletely understood.